Autoimmune disorders associated with myelodysplastic syndromes: clinical, prognostic and therapeutic implications. (June 2022) - Fozza, Claudio; Murtas, Andrea; Caocci, Giovanni; La Nasa, Giorgio
Abstract: Around one third of patients with myelodysplastic syndromes (MDS) suffer from concomitant autoimmune disorders (AD). However the actual burden of such an association appears to be quite heterogeneous in different studies probably due to variable criteria in selecting both MDS patients and subtypes of AD. Moreover, both the prognostic implications and the potential applications of specific therapeutic approaches in this patient subgroup are still at least partially under debate. The present review will try to shed some further light on the clinical association between MDS and AD in order to better delineate its prognostic significance and to suggest potential therapeutic algorithms available for these patients. Highlights: 20–30% of myelodysplastic syndromes (MDS) are associated with autoimmune disorders (AD). Largest studies show for these patients a better survival or no prognostic impact. Most AD associated with MDS are efficiently managed with immune-therapeutic treatments. The resolution of some AD after MDS-modifying therapeutic approaches is reported.